Thioether-functionalized trifluoromethyl-alkynes, 1, 3-dienes and allenes: divergent synthesis from reaction of 2-trifluoromethyl-1, 3-conjugated enynes with sulfur nucleophiles. Issue 59 (4th October 2018) - Cheng, Huayu; Zhou, Xiaofan; Hu, Anjing; Ding, Shiteng; Wang, Yimo; Xiao, Yuanjing; Zhang, Junliang
Abstract : A divergent synthesis of thioether-functionalized trifluoromethyl-alkynes, 1, 3-dienes and allenes viaregioselective nucleophilic addition of sulfur nucleophiles to 2-trifluoromethyl-1, 3-conjugated enynes was developed. Abstract : A divergent synthesis of thioether-functionalized trifluoromethyl-alkynes, 1, 3-dienes and allenes via regioselective nucleophilic addition of sulfur nucleophiles to 2-trifluoromethyl-1, 3-conjugated enynes was developed. The addition patterns depend on the type of enyne, sulfur nucleophile and reaction conditions used. 1, 4-Addition leading to thioether-functionalized trifluoromethyl-allenes was realized when enynes possessing electron-withdrawing aryl groups on the alkyne moiety were used as reaction partners and alkanethiols were used as nucleophiles, whereas solvent-controlled construction of thioether-functionalized 1, 3-dienes and alkynes was realized, respectively, via a 3, 4-addition pattern or 1, 2-addition pattern if thiophenols were applied as nucleophiles. The three types of compounds containing both sulfur and fluorine elements are valuable building blocks for synthesis of multifunctional fluorinated vinyl sulfides and thiophene derivatives.